The Application of MR Spectroscopy and MR Perfusion in Cerebral Syphilitic Gumma: A Case Report - Cui, Linyang; Liu, Jie; Zhang, Wenjun; Xu, Zushan; Hou, Hongjun (Frontiers in Neuroscience, 2020)
Cerebral syphilitic gumma is a rare disease and can be misdiagnosed as a common brain tumor when only conventional imaging results are adopted. Differentiating between syphilitic gumma and tumors may be achieved by applying advanced magnetic resonance (MR) techniques, such as MR spectroscopy and MR perfusion. However, the MR perfusion characteristics of cerebral syphilitic gumma have not been reported yet. Here, we report a case of cerebral syphilitic gumma in a 52-year-old woman, and discuss the imaging features of conventional MR, MR spectroscopy and MR perfusion. The results suggest that the application of MR spectroscopy and MR perfusion could provide additional information which contributes to the diagnosis of cerebral syphilitic gumma.